Analisis Pentingnya Branding dan Storytelling Produk Manco agar Lebih Dikenal di Luar Madiun - Tia Rahel Amanda; Ulan Novinta Mariska (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Manco, a traditional snack from Madiun, holds significant potential to grow and gain recognition beyond its region of origin. Its unique taste, texture, and embedded cultural and historical values serve as key assets in an increasingly competitive market. However, the main challenges faced by manco entrepreneurs are building a strong brand identity and conveying the product’s uniqueness through engaging storytelling. Effective branding through distinctive logos, packaging, and memorable taglines can enhance the product’s appeal and perceived value among consumers. Furthermore, compelling storytelling, such as narratives about traditional production processes, the struggles of business owners, and the use of natural ingredients, can foster emotional connections and consumer loyalty. Nevertheless, challenges remain, such as inconsistent brand identity usage and limited digital promotion. Therefore, branding and storytelling training are essential for manco entrepreneurs to maximize their product’s potential, expand their market, and establish manco as a culinary icon representing Madiun both nationally and internationally.